PENGARUH KEMAMPUAN INDIVIDU DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA MELALUI KEPUASAN KERJA PEGAWAI PADA KANTOR BAWASLU KABUPATEN BARRU - Marsuki Umar; Saban Echdar; Maryadi Maryadi (AkMen JURNAL ILMIAH, 2020)
The purpose of this study was to analyze the direct and indirect effects between individual abilities and work environment on work morale through employee job satisfaction at the Barru District Bawaslu Office. In this study, researchers used a type of descriptive research with a quantitative approach. The population in this study were all employees in the Barru Regency Government Office as many as 101 people, so the sample technique used was saturated samples. Hypothesis testing is done using path analysis techniques and the sobel test. The results of this study indicate that: Individual ability and work environment directly have a positive and significant effect on job satisfaction and employee morale at the Barrulu Bawaslu office. Likewise the indirect effect of the work environment also has a positive and significant effect on morale through employee job satisfaction in the Bawaslu office of Barru Regency. While the individual's ability indirectly has a positive but not significant effect on morale through employee job satisfaction at the Barru Regency Bawaslu office.